The Relationship Between Diet Quality And Body Weight Management In Pre-Obese And Obese Women - Dagoglu, Irem; Persil-Ozkan, Ozlem (Mattioli 1885, 2022)
Objectives: The aim of this study was to investigate the relationships between KIDMED, Mediterranean Diet Quality Index, Diet Quality Index International (DQI-I) scales and Body Mass Index (BMI), body fat percentage, biochemical parameters of preobese and obese women. Methods: This descriptive and cross-sectional study was conducted on 125 participants who applied to Firat University Hospital Nutrition and Diet Policlinic between 11 April 2019 and 31 May 2019 in Elazig/Turkey. Nutritional habits were evaluated with KIDMED and DQI-I. Food frequency questionare was used to collect data on dietary patterns. Chi-square test, T-test, ANOVA were used to analyze data. Scheffe or Tamhane tests were used in the binary comparisons of the groups. Pearson Correlation was used to evaluate the relation of quantitative variables with each other. Results: The mean age of the participants was 39,09 +/- 14,36 (min 19- max 69) years and %52 (n:65) were pre-obese and % 48 (n:60) were obese according to BMI. Mean scores of KIDMED and DQI-I of pre-obeses were significantly higher than obeses. BMI, body fat percentage, total cholesterol level were inversely associated with both DQI-I and KIDMED. The relationship between total cholesterol level and dietary total fat, saturated fat, cholesterol, empty calorie food, and fatty acid ratio scores was negatively significant for each component. Conclusion: The majority of pre-obese people were in the good and average categories of KIDMED, while the obese were mostly in the average and poor categories.The relationship between BMI and DQI-I total score was stronger than KIDMED.
Keywords: Diet quality; Mediternean diet; Obesity; Body fat; Nutritional behaviours